2020
DOI: 10.3390/ijms21228698
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites of the Rice Blast Fungus Pyricularia oryzae: Biosynthesis and Biological Function

Abstract: Plant pathogenic fungi produce a wide variety of secondary metabolites with unique and complex structures. However, most fungal secondary metabolism genes are poorly expressed under laboratory conditions. Moreover, the relationship between pathogenicity and secondary metabolites remains unclear. To activate silent gene clusters in fungi, successful approaches such as epigenetic control, promoter exchange, and heterologous expression have been reported. Pyricularia oryzae, a well-characterized plant pathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 131 publications
0
16
0
1
Order By: Relevance
“…Pyricuol (247) exhib-ited stronger phytotoxic activity toward rice than pyriculol (244) and dihydropyriculol (245) [182]. It has been shown that aldehyde derivatives induced lesion-like necrosis on rice leaves, while alcohol derivatives were inactive [183]. Epipyriculol (246) was isolated from the cultures of Pyricularia oryzae.…”
Section: Phenols and Phenolic Acidsmentioning
confidence: 99%
“…Pyricuol (247) exhib-ited stronger phytotoxic activity toward rice than pyriculol (244) and dihydropyriculol (245) [182]. It has been shown that aldehyde derivatives induced lesion-like necrosis on rice leaves, while alcohol derivatives were inactive [183]. Epipyriculol (246) was isolated from the cultures of Pyricularia oryzae.…”
Section: Phenols and Phenolic Acidsmentioning
confidence: 99%
“…The secondary metabolites in Pyricularia oryzae, including melanin and phytotoxic pyriculols, are both required for the infection (Motoyama, 2020). Glyoxylate and dicarboxylate metabolism and lipid metabolism can provide important metabolic intermediates and energy for the development of fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary metabolites produced by plant pathogenic fungi play an important role in pathogenicity during pathogenic interactions with plants (Macheleidt et al., 2016). The secondary metabolites in Pyricularia oryzae , including melanin and phytotoxic pyriculols, are both required for the infection (Motoyama, 2020). Glyoxylate and dicarboxylate metabolism and lipid metabolism can provide important metabolic intermediates and energy for the development of fungi.…”
Section: Discussionmentioning
confidence: 99%
“…The structures of these compounds are related to zopfinol, but most of them were not active, except for one of the salicylaldehyde derivatives, which showed weak activity against Mycobacterium tuberculosis and Bacillus cereus [ 54 ]. Other compounds with structures related to zopfinol and its derivatives are the salicylaldehyde sordarial produced by Neurospora crassa , which also belongs to the order Sordariales [ 55 ], and the pyriculols, which are phytotoxic polyketides produced by the sordariomycete phytopathogenic fungus Pyricularia oryzae [ 56 ]. Since the phytotoxic pyriculol [ 57 ] differs from 2 only in the length of its aliphatic side chain, it would be highly interesting to test the phytotoxicity of zopfinols.…”
Section: Discussionmentioning
confidence: 99%